Attitudes of students of Zakho University toward Kurdish language-converting curriculum and their relation with some variables - Mohammed, Nasraddin (Humanities Journal of University of Zakho, 2022)
The aim of the study is to testify the statistical hypotheses concerning the significant differences between attitudes of a sample of students of Zakho University toward Kurdish language-converting curriculum in Kurdistan region universities and their relation with some variables (gender, specialization, age and class), the sample of the study consists of (235) students of the university, which have been selected randomly. For this purpose researcher prepared a questionnaire include of (32) items. The results of the study showed that members of research’s sample have positive attitudes toward Kurdish language-converting curriculum and also there is no statistical significant difference among them according to the study’s variables, and in the light of these results researcher gives some suggestions and recommendations.